Applying IWATE criteria to robotic hepatectomy: is there a "robotic effect"?. Issue 6 (June 2021) - Luberice, Kenneth; Sucandy, Iswanto; Modasi, Aryan; Castro, Miguel; Krill, Emily; Ross, Sharona; Rosemurgy, Alexander
Abstract: Background: The objective of this study is to apply this criteria to determine its applicability to robotic hepatectomy. Methods: We prospectively followed 105 patients undergoing robotic hepatectomy. Operations were categorized into Low (0–3), Intermediate (4–6), Advanced (7–9), and Expert (10–12). Results: Patients had a median age of 62 (61 ± 13.1) years, with a BMI of 28 (29 ± 6.1) kg/m 2 ; 38% were women. ASA class was 3 (3 ± 0.6). Of the 105 operations, 2 were categorized as Low, 31 as Intermediate, 49 as Advanced, and 23 as Expert. EBL and operative duration were found to be significantly greater as the operative difficulty level increased (p < 0.03 and p < 0.01, respectively). Intraoperatively, when comparing Expert and Intermediate, EBL and operative duration were significantly greater (p = 0.0001 and p = 0.0031, respectively). In the comparison of Expert with Advanced, operative duration was significantly longer (p = 0.0001). Postoperatively, comparisons between Expert and Intermediate, Expert and Advanced, and Advanced and Intermediate showed no differences. Conclusion: EBL and operative duration increased with IWATE scores reflecting more difficult robotic hepatectomies. However, with the robotic approach, our postoperative outcomes were similar irrespective of IWATE difficulty scores. Perhaps, the robotic approach potentially has a mitigating effect on postoperative outcomes regardless of difficulty level.